Vloga tržnega komuniciranja pri oblikovanju ugleda bank - Završnik, Bruno (Naše gospodarstvo, 2006)
Corporate reputation is one of the key elements of success for every company on today's globally competitive market. In order to obtain a positive corporate reputation, it is necessary to know and understand all features of corporate reputation management. This article presents the key elements of corporate reputation and which tools of marketing communication mix are most effective for forming and executing company communication in order to ensure abank's long term positive reputation.
Keywords: bančništvo; marketing; banke; kvaliteta; trženje; tržno komuniciranje; strategija trženja; poslovni ugled; javnost; komuniciranje; communication